Refleksi Emosional: Cinta dan Kecemasan dalam Karya Ibn Hazm - Andri, Rival; Nurholis, Nurholis; Pratiwi, Nabila Putri; Yasis, Rizqia Fatimatuzahra; Fhadilla, Ghulam Ikhwan (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2025)
This analysis explores two central themes in Ibn Hazm’s works—love and anxiety—by examining their interplay and impact on human behavior. Through a close reading of Tawq al-Hamamah (The Dove’s Neckring) and Filsafat al-Akhlaq wal-Siyar (Philosophy of Morals and Conduct), the study reveals Ibn Hazm’s view of love as a profound yet complex experience that engenders not only joy but also anxiety, longing, and uncertainty. Anxiety, in Ibn Hazm’s framework, arises as a natural response to relational vulnerability and moral responsibility. Furthermore, the analysis highlights his proposed remedies for anxiety, emphasizing character development, ethical practice, and spiritual connection with God. Employing an interdisciplinary approach—integrating literary studies, psychology, and moral philosophy—this research enriches understanding of emotional dynamics in classical Islamic thought while underscoring its relevance to modern life, where love and anxiety remain universal human experiences. The findings aim to inspire further studies on the intersection of emotion, morality, and spirituality in Islamic intellectual tradition and its dialogue with contemporary perspectives. Abstrak Analisis ini mengeksplorasi tema utama dalam karya-karya Ibn Hazm cinta dan kecemasan dengan meneliti interaksi dan dampaknya terhadap perilaku manusia. Melalui pembacaan yang cermat terhadap Tawq al-Hamamah (Cincin Leher Merpati) dan Filsafat al-Akhlaq wal-Siyar (Filsafat Moral dan Perilaku), penelitian ini mengungkap pandangan Ibn Hazm tentang cinta sebagai pengalaman yang mendalam namun tidak hanya menimbulkan kegembiraan tetapi juga kecemasan, kerinduan, dan ketidakpastian. Kecemasan, dalam kerangka Ibn Hazm, muncul sebagai respons alami terhadap kerentanan relasional dan tanggung jawab moral. Lebih jauh, analisis ini menyoroti solusi yang diusulkannya untuk kecemasan, menekankan pengembangan karakter, praktik etika, dan hubungan spiritual dengan Tuhan. Dengan menggunakan pendekatan interdisipliner mengintegrasikan studi sastra, psikologi, dan filsafat moral penelitian ini memperkaya pemahaman tentang dinamika emosional dalam pemikiran Islam klasik sambil menggarisbawahi relevansinya dengan kehidupan modern, di mana cinta dan kecemasan menjadi pengalaman manusia yang universal. Temuan ini bertujuan untuk menginspirasi tentang persimpangan emosi, moralitas, dan spiritualitas dalam tradisi intelektual Islam.